The Influence of Live Streaming and Content Marketing on Purchasing Decisions on TikTok Social Media - Bayu Saputro; Sulartopo, Sulartopo; Siti Kholifah; Febryantahanuji, Febryantahanuji; Haryo Kusumo (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The growth of digital technology has led to a change in how marketing is done, moving away from traditional methods to using social media for marketing. TikTok is a popular platform that lets people stream live videos and promote their content, which can affect how people make buying choices. This study looks at how live streaming and content marketing affect TikTok users. A quantitative method was used, which involved giving out questionnaires to 100 people from Generation Z in Bojonegoro Regency. Researchers used multiple linear regression to figure out how much each variable influenced the outcome. The findings show that both live streaming and content marketing have a positive and important effect on how people make buying decisions, whether on their own or together. Content marketing was found to have a stronger impact than live streaming. Both variables helped explain a large part of why consumers make their buying choices.